The Significance of the Bernardine Fund in the Study of Historiographical Narratives on Kmicic’s Armia Krajowa Brigade - Božerocki, Tomaš (Knygotyra, 2020)
During World War II, in 1939–1944, there was a Polish armed resistance movement in Eastern Lithuania, which was called Armia Krajowa (Home Army) in the abstract. In researching the activities of Armia Krajowa (AK) in Eastern Lithuania, not only historiography is valuable, but also surviving documents and memoirs, as well as the Bernardine Fund preserved in the Lithuanian Central State Archives. So far, this Fund does not seem to receive much attention from scientists researching the activities of AK in Lithuania, as well as archives compiled by Poles residing in other countries. Based on the concept of storage medium, the article analyzes the case of the Bernardine Fund in the context of archival research of the Polish diaspora. During the analysis of the documents kept in the Bernardine Fund, it was observed that the said Fund held significant documents that could supplement / replace the existing narrative about Kmicic’s AK partisan brigade. Kmicic’s AK partisan brigade is noteworthy, as it is the first armed AK unit to launch a consistent armed resistance, but so far there are no separate studies dedicated to the activities of this brigade. The storage medium is the basis of memory communication that gives authenticity to the constructed memory narrative. The Bernardine Fund is a storage medium that originated in the past and reached the present unchanged / slightly changed, and that contains a certain memory narrative about AK. The Bernardine Fund and the documents contained in it are valuable storage media that can help reveal the situation of the residents of Eastern Lithuania during World War II and shed new light on the military activities of AK. In the context of research and preservation of the written heritage of the Polish diaspora, this medium has not yet received the attention of scientists, although the example of the Kmicic’s AK brigade proved that this Fund contains documents that reveal hitherto unknown aspects of AK activities. A fact turns into an event only when certain groups draw their attention to it, when they give meaning to it and start talking and writing about it, and it begins to be remembered. All significant events are just someone’s creations, created just to justify the present in a way that is convenient for the collective, the political elite, or the heads of state. The case of Kmicic’s brigade has proven that no fact is completely lost. If a fact is not currently updated and used, it does not mean that it will be the case all the time. The documents kept in the Fund reflect that during the formation of the historiographical narrative, the collective memory of the said brigade, part of the events was deliberately omitted in order to give integrity to the narrative being formed.